Monte Carlo Simulation Approach To Improve Overburden Operational Performance: Case Study of PT Bukit Asam TBK - Fithri Halim Ahmad; Nur Budi Mulyono (Dinasti Publisher, 2025)
This research develops a data-driven approach to improve overburden operational performance at PT Bukit Asam Tbk by utilizing Monte Carlo simulation as the primary analytical tool. Simulation results identified two main operational constraints. First, although the Matching Factor between loading and hauling equipment was balanced, the total fleet capacity was insufficient to achieve production targets. Second, poor synchronization (evidenced by high occurrences of “Wait Hauler” and “No Hauler” standby time) contributed to low Use of Availability (UA) and Equipment Utilization (EU), which reduces Effective Working Hours (EWH). First is to give addition to the fleet setting in East Pit 3, and second is to implement a real-time Mine Traffic Control (MTC) system. The proposed solutions were tested through simulation. Results showed that equipment addition could increase production by up to 26.8% and improve productivity by 1.76%. Meanwhile, the MTC system was projected to reduce controllable standby by 10.44%, increase EWH by 4.77%, and raise production under stable productivity conditions to 4.77%. Overall, the use of simulation and data-driven strategies proves effective in identifying root causes, designing measurable interventions, and validating their impact on productivity. The findings offer practical insights for improving operational efficiency of mining equipment operations in PT Bukit Asam Tbk